Variations in Food Choices of Long-Tailed Monkeys (Macaca fascicularis) in the Pulaki Temple Area, Gerokgak District, Buleleng Regency - Syah, Moh Jafron; Yuliastuti, Yuliastuti; Safitri, Mely (Al-Hayat: Journal of Biology and Applied Biology, 2024)
AbstractMacaca fascicularis, included in the Cercopithecidae family, have a significant ecological role, one of which is as a disperser of seeds from the fruits they consume. M. fascicularis is tolerant to different types of natural and non-natural food (human food waste and rubbish), so it is currently an omnivorous animal. It can be found not only in primary and secondary forests but also in habitats close to human activity. M. fascicularis in Bali can be found in sacred areas such as temples, one of which is in the Pulaki temple area. This research aimed to determine the variety of food choices of M. fascicularis in the Pulaki temple area. This research was conducted from June to October 2023. M. fascicularis in the Pulaki Temple area was divided into four groups: Madya, Medal, Pabean, and Parkiran. The daily activities of M. fascicularis observed in this study were sleeping, grooming, sexual activity, moving, eating, caring for children, playing, and agonistic (violent activity). Based on calculations, the consumption of non-natural foods had a higher frequency (87.18%) than natural foods (12.78%). During the research, M. fascicularis in the Pura Pulaki area had the highest preference for Gemitir flowers (n=2299). Gemitir flowers are one of the offerings fillings by Hindus who perform prayers. The high consumption of non-natural food by M. fascicularis in this area was due to several factors, namely, the lack of natural food sources and the low level of human awareness for not providing non-natural food, thus changing the animals' natural behavior. This behavior change could alter the role of animals in the ecological niche, thereby reducing the balance of the ecosystem. Therefore, it is necessary to maintain the natural behavior of animals by increasing natural food sources and creating clear rules regarding the prohibition of feeding animals to visitors.